Предмет: Алгебра,
автор: Kipriot
Решите пожалуйста задание
Приложения:
Ответы
Автор ответа:
0
= (log(4*3) - log3 + 9log9 (2^3)) lg3=(log(2^2)+log3-log3+9* (log(2^3) / log9)lg3=
=(2log2+(9 * 3log2 /log(3^2)) *lg3=(2 + 27 / 2 log3) lg3= ((4log3+27) /2log3) lg3=
log3; log2 везде основание 2! log2 (2)=1 ; Может в конце не lg???
=(2log2+(9 * 3log2 /log(3^2)) *lg3=(2 + 27 / 2 log3) lg3= ((4log3+27) /2log3) lg3=
log3; log2 везде основание 2! log2 (2)=1 ; Может в конце не lg???
Автор ответа:
0
В конце lg
Похожие вопросы
Предмет: Обществознание,
автор: alisa3003
Предмет: Информатика,
автор: alim150708
Предмет: Английский язык,
автор: Аноним
Предмет: Математика,
автор: ssvobodnaia